Morphological, geographic and ecological evidence support a new species of Chusquea subg. Swallenochloa (Poaceae, Bambusoideae, Bambuseae) from Parque Nacional do Caparaó, Brazil - Pianissola, Evandro M.; S. Gonçalves, Ana Paula; G. Clark, Lynn; Oliveira, Reyjane P. (Phytotaxa, 2023)
Specimens from the Serra do Caparaó (border of Minas Gerais and Espírito Santo states in Brazil) previously treated as Chusquea aff. heterophylla were compared with C. heterophylla. We found differences in macromorphology (including habit, culm leaf persistence and indument, subsidiary branch number, foliage leaf indument on sheath and blades, and spikelet size and bract proportions), abaxial micromorphology of the foliage leaf blades (including silica cell shape, prickle hair shape, bicellular microhair relative size and proportion of its cells, macrohair presence, long cell papillar shape, and subsidiary cell papillar shape and orientation) and in geographic distribution and habitat. These differences were considered enough to describe Chusquea riparia as a new species herein considered as microendemic to the Parque Nacional do Caparaó, growing only in riparian areas of montane Atlantic forest and campos de altitude. We provide illustrations, maps, taxonomic and phenological comments on the new species, and a key to the species of C. subg. Swallenochloa from the Parque Nacional do Caparaó.